2015
DOI: 10.1099/vir.0.000133
|View full text |Cite
|
Sign up to set email alerts
|

Porcine epidemic diarrhea virus infection induces NF-κB activation through the TLR2, TLR3 and TLR9 pathways in porcine intestinal epithelial cells

Abstract: Porcine epidemic diarrhea virus (PEDV) is a coronavirus that induces persistent diarrhoea in swine, resulting in severe economic losses in swine-producing countries. Insights into the interplay between PEDV infection and the innate immune system are necessary for understanding the associated mechanism of pathogenesis. The transcription factor NF-kB plays an important role in regulating host immune responses. Here, we elucidated for the first time to our knowledge the potential mechanism of PEDV-mediated NF-kB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 44 publications
4
76
0
Order By: Relevance
“…Data showed that the inflammatory cytokines (such as IL-1β, IL-6, IL-8, CCL5, TNF-α, and MCP-1) were significantly down-regulated at 24 hpi when autophagy was inhibited in PEDV infected cells (Figure 6A,B), suggesting the potential involvement of autophagy in PEDV induced inflammation. It is well-known that the NF-κB signaling pathway plays a pivotal role in PEDV induced inflammatory response and Vero cells are interferon deficient [19,29]. Therefore, the influence of autophagy on the NF-κB pathway was determined under the deficient expression of Beclin1 and ATG5 at 24 h upon PEDV infection by immunoblotting analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Data showed that the inflammatory cytokines (such as IL-1β, IL-6, IL-8, CCL5, TNF-α, and MCP-1) were significantly down-regulated at 24 hpi when autophagy was inhibited in PEDV infected cells (Figure 6A,B), suggesting the potential involvement of autophagy in PEDV induced inflammation. It is well-known that the NF-κB signaling pathway plays a pivotal role in PEDV induced inflammatory response and Vero cells are interferon deficient [19,29]. Therefore, the influence of autophagy on the NF-κB pathway was determined under the deficient expression of Beclin1 and ATG5 at 24 h upon PEDV infection by immunoblotting analysis.…”
Section: Resultsmentioning
confidence: 99%
“…While the ligand that activates TLR4 signaling following SARS-CoV infection has not yet been identified, our group has recently shown that TLR4 deficient mice are highly susceptible to SARS-CoV infection (Totura et al 2015). Other laboratories have demonstrated the importance of TLRs in the host immune response to porcine epidemic diarrhea virus (PEDV) (Cao et al 2015) and mouse hepatitis virus (Mazaleuskaya et al 2012), supporting a general requirement for TLR signaling in an effective immune response to coronavirus infection. TLR4 is classically known as the LPS receptor (Poltorak et al 1998), but it can also recognize host proteins that have altered expression under conditions of cell stress, such as heat shock proteins and proteins involved in the extracellular matrix (ECM) like fibrinogen, heparin sulfate, and hyaluronic acid (Okamura et al 2001; Smiley et al 2001; Cohen-Sfady et al 2005; Akbarshahi et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The sequences of specific siRNA oligonucleotides were as follows. TLR-sense: CCAGAUCUUUGAGCUCCAUTT; antisense: AU GGAGCUCAAAGAUCUG GTT; negative control-sense: UUCUCCGAACGUGUCACGUTT; antisense: ACGUG ACACGUUCGGAGAATT [55]. …”
Section: Methodsmentioning
confidence: 99%